Analysis of the implementation of the national Roma integration strategy 2012-2020 - Nicolás Lizama, Mercedes (Avances en Supervisión Educativa, 2016)
This article aims to provide a contribution to the process of implementation of the National Roma Integration Strategy 2012-2020 and the impact on improving discrimination and social inclusion of this group. Four years have passed since its launch and, pending the evaluation report that will be made at the end of 2016, the forecast based on interim reports by the European Commission, the Spanish Government and Roma organizations such as FSG, it is not satisfactory enough. The areas related to education, employment, housing and discrimination remain being the least advanced. Despite the existence of improvements, they still need to intensify the efforts to combat discrimination and improve the integration of Roma population.
Keywords: Roma; discrimination; social insertion; public policy; National Roma Integration Strategy